Czy nadchodzi śmierć tekstu? Kilka refleksji na marginesie teorii technologicznego determinizmu - Klichowski, Michał (Wydawnictwo Naukowe UAM, 2012)
This article presents the theory of technological determinism. It shows the correlation of modern technological change and changes in the approach to reading a text. It presents the results of a quasi-experiment relating to this context and their interpretations and formulates a hypothesis concerning the impending death of the text.
Has the Death of the Text Come? Some Reﬂections on the Margins of the Theory of Technological Determinism
Keywords: education; technological determinism; textuality